MENGEMBANGKAN KECERDASAN LOGIS MATEMATIK PADA ANAK USIA DINI MELALUI METODE CERITA BERGAMBAR MODEL POP UP KELOMPOK B - Desy Eka Putri; Siti Nurinayah; Fifiet Dwi Tresna Santana; Dewi Safitri Elshap (IKIP Siliwangi, 2019)
This research was conducted to find out the differences from the learning methods of ordinary pictorial stories with the pop up models of the more unique and different pop up models, but also through this research it is hoped to provide new experiences for children, bearing in mind that learning is still focused on writing, reading and counting (calistung). This study uses the experimental method because there is a comparison between the control class and the experimental class. The subject and location of the study were group B students. The study population was the B-Saturn group and the B-Uranus group with a sample students, with a total of 28 students. Data collection techniques using pretest and posttest. Pretest technique using ordinary picture stories while in the posttest technique using picture models pop up. Results of Research The average value (mean) in the control class is BB (1.21), MB (0.21), BSB (0.42) and BSH (0.14) while in the experimental class the average value is BB (0.29), MB (0.21) , BSB (0.5) and BSH (0.14). Then it can be concluded that